Political Catholicism and Euroscepticism: the deviant case of Poland in comparative perspective - Napieralski, Bartosz (BASEES / Routledge series on Russian and East European studies, 2017)
Setting the scene, Euroscepticism, religion and politics -- The nature of political Catholicism -- Political Catholicism in Poland -- Party-based Euroscepticism in Poland and the role of political Catholicism -- Political Catholicism and Euroscepticism, the deviant case of Poland -- Political Catholicism and European integration, a comparative perspective -- Religion and Euroscepticism